Bounded absorbing sets for compressible non-Newtonian fluids: 76A05 , 35Q35 - Muhammad, Jan (Journal of engineering mathematics, 2024)
In this article, we investigate non-Newtonian compressible fluid in three-dimensional bounded domain with a compact Lipschitz boundary driven by bounded forces. We investigate the existence result with bounded absorbing sets for weak solutions of considered fluid, while the adiabatic constant γ is subject to some specific restrictions.